Dialectical perspective and treatment in poetry of Khalil Hawi (Journal of the College of Education for Women, 2019)
Were not experience Khalil Hawi capillary module as presented or routine in the formatof the implications , but was saturated transitions quality that targeted built by visionary andmechanisms expressive , Valgosaidp when the container is a clash between two worlds worldNahdi to promote world on the ashes , and often strained poet himself to achieve an approachbetween worlds , and in the midst of those caesarean section exhausted poet in touch his toolsand visions , and this is why the poetry Hawi toward westernization expressive as a result ofthe conflict concepts chronic , be sure to researcher not engaged in the overall qualitativechanges in the structure and content, but the goal Acetknah level that qualitativetransformation Visionary First , the nature of employment in the automated charging thattransformation and enlightenment